An Analysis of the Development of Pet Insurance Market in UK and China - He, Liu (2008)
In the uncertain society, people pay insurance on everything, now the trend turns to small animals. The purpose of this study is to understand the differences between two pet insurance markets, where one is developed in UK and the other is in China. Moreover, overview of pet insurance in USA, Sweden and Japan will be attached to set out their perfect operation systems. Based on this analysis, Chinese insurers seek to obtain strategic management experience and coverage setting issue from the international insurance market practitioners. This dissertation collects data by employing online survey and uses SPSS approach to analyse the results. The main findings are China has huge potential to be the next outstanding country of pet insurance sale, however, local insurance companies who sell pet insurance should adjust their present policies and conditions, also the governmental regulatory body (e.g. the China Insurance Regulatory Commission, CIRC) should upgrade relative rules or laws with the development of insurance market.